2019
DOI: 10.1186/s12884-019-2660-5
|View full text |Cite
|
Sign up to set email alerts
|

Unrecognized maternal heart rate artefact in cases of perinatal mortality reported to the United States Food and Drug Administration from 2009 to 2019: a critical patient safety issue

Abstract: BackgroundMaternal heart rate artefact is a signal processing error whereby the fetal heart rate is masked by the maternal pulse, potentially leading to danger by failure to recognize an abnormal fetal heart rate or a pre-existing fetal death. Maternal heart rate artefact may be exacerbated by autocorrelation algorithms in modern fetal monitors due to smooth transitions between maternal and fetal heart rates rather than breaks in the tracing. In response, manufacturers of cardiotocography monitors recommend ve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 27 publications
(21 reference statements)
1
12
0
Order By: Relevance
“…13 Another limitation of traditional CTG-based FHR measurements relates to the impact of MHR artifacts, which can result in potentially dangerous consequences for the fetus. 25 Although a noninvasive system to measure FHR will inherently capture maternal recordings, the large amplitude of the maternal signal ensures that it can be captured with sufficient signal-to-noise ratio to validate it and eliminate it from the raw signal. In contrast to strategies that rely on a single or a few biosensors to capture FHR and MHR signals, the use of data from multiple biosensors (8 ECG and 4 acoustic) in the Invu system allows the algorithm to remove the maternal ECG from contaminating the fetal ECG, essentially performing signal ambiguity detection, thereby reducing artifacts and the likelihood of errors in FHR calculation and interpretation.…”
Section: Original Researchmentioning
confidence: 99%
“…13 Another limitation of traditional CTG-based FHR measurements relates to the impact of MHR artifacts, which can result in potentially dangerous consequences for the fetus. 25 Although a noninvasive system to measure FHR will inherently capture maternal recordings, the large amplitude of the maternal signal ensures that it can be captured with sufficient signal-to-noise ratio to validate it and eliminate it from the raw signal. In contrast to strategies that rely on a single or a few biosensors to capture FHR and MHR signals, the use of data from multiple biosensors (8 ECG and 4 acoustic) in the Invu system allows the algorithm to remove the maternal ECG from contaminating the fetal ECG, essentially performing signal ambiguity detection, thereby reducing artifacts and the likelihood of errors in FHR calculation and interpretation.…”
Section: Original Researchmentioning
confidence: 99%
“…According to Reinhard et al [5], MHR periods are found in up to 90% of intrapartum recordings and account for 6.2% of the duration of the recording. This problem is particularly frequent during the second stage of delivery and can be particularly dangerous for the fetus [6,7]. For example, France's Melchior classification (used to describe the second stage of delivery [8]) suggests an erroneous type 3 FHR pattern (corresponding to bradycardia plus accelerations synchronized with uterine contractions (UCs), and for which expulsive efforts should last for less than 15 min) these cases (accounting for ≈ 4% of deliveries) correspond in fact to MHR interferences [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The software in CTG monitors sometimes also comprises an alert system based on coincidence between the MHR and FHR channels [7]. However, these coincidences have to be checked manually.…”
Section: Introductionmentioning
confidence: 99%
“…According to Reinhard et al [5], MHR periods are found in up to 90% of intrapartum recordings and account for 6.2% of the recording. This problem is particularly frequent during the second stage of delivery and can be particularly dangerous for the fetus [6,7]. For example, France's Melchior classification used to describe the second stage of delivery [8] proposed erroneously the type 3 FHR pattern (corresponding to bradycardia plus accelerations synchronized with the uterine contractions (UC), and for which expulsive efforts should be less than 15 min) whereas all those cases (representing ≈ 4% of deliveries) are in fact FS of MHR [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The software in CTG monitors comprises also sometime an alert system based on coincidence between MHR and FHR channels [7]. However, these coincidences have to be checked manually.…”
Section: Introductionmentioning
confidence: 99%